A comprehensive review on propagation techniques of the medicinal herb Ocimum tenuiflorum L. - Thi-Hoan Luong; Dang-Minh-Chanh Nguyen (Vietnam Journal of Science, Technology and Engineering, 2025)
Ocimum tenuiflorum L. (holy basil) is an economically important medicinal plant widely valued for its diverse therapeutic properties and applications in traditional medicine, food, cosmetics, and pharmaceuticals. The growing global demand for holy basil and its essential oil has driven interest in efficient propagation methods to ensure a consistent supply of high-quality planting materials. This review provides a comprehensive analysis of sexual propagation, clonal propagation, and tissue culture techniques, critically evaluating their advantages, limitations, and scalability for commercial production. Key production bottlenecks, including low seed germination uniformity, limited rooting efficiency in cuttings, and high tissue culture costs, are identified, and strategies are proposed to optimise propagation efficiency and reduce costs. These insights provide a foundation for future breeding programs, sustainable cultivation, and industrial applications of O. tenuiflorum.